Multimodal imaging of tibialis anterior muscle adaptations to neutral-position immobilization - Sheiren A. Martínez-Méndez; Berenice Martínez-Gutierrez; Zuriel Casillas-Marquez; Bertha Segura-Alegria; Iván Rosado-Méndez; Carla P. Villanueva-Meléndez; Ismael Jimenez-Estrada; Karla García-Pelagio (PLoS ONE, 2026)
Muscle disuse atrophy is a frequent consequence of therapeutic immobilization following sport injuries, bone fractures, and ligament tears, often resulting in marked reduction of muscle volume, mass, and strength. Despite the widespread use of neutral-position limb immobilization in clinical practice, its physiological effects remain insufficiently characterized. To address this gap, we employed thermographic, tomographic, and ultrasound imaging to assess how neutral-position immobilization (Imm) affects the tibialis anterior, a predominantly fast-twitch ankle dorsiflexor muscle that plays a key role in foot deceleration after heel strike, provides functional stability during gait preventing falls and contributes substantially to load absorption, in twenty-seven young male Wistar rats after 7 and 14 days of treatment. To complement these, force measurements and histology were analyzed. Our results showed a significant limb temperature increase of up to 10% after 14 days compared to controls accompanied by a volume reduction of 38% (p < 0.05) confirmed by tomography and a 2-fold (p < 0.05) increment of CNFs denoted by histology (H&E). At 14 days of Imm ultrasound imaging highlighted changes in subcutaneous tissue thickness, and increased connective tissue; a significant 2-fold reduction in specific force during muscle twitch and 28% (p < 0.05) in tetany. Fiber type conversion mainly to type IIA (intermediate) was evident on histology and supported by the prolonged fatigue time following two fatigue protocols (continuous stimulation and repeated short-tetany) for up to 50% (p < 0.05) after 14 d of Imm. Our results demonstrate that, although immobilization in a neutral position is the best practice in the clinic, it carries important detrimental changes in muscle structure and physiology. These findings underscore the importance of integrating clinical imaging techniques to monitor muscle status during immobilization and rehabilitation, enabling more effective and timely interventions.